Effects of trimetazidine on oxidant-antioxidant balance and angiogenesis; an in vivo experimental study - Fethullah Kayan; Hasan Basri Savas (BMC Cardiovascular Disorders)
Abstract Background We evaluated the effects of trimetazidine (TMZ) on the oxidative-antioxidative balance and angiogenesis in an in vivo experimental model. This study aims to evaluate the effects of trimetazidine on angiogenesis through histological analysis and to assess its impact on oxidative-antioxidative balance through biochemical measurements. Methods In this study, Ross 308 breed chicken eggs (n = 40) were used, and embryos were divided into four distinct groups. On the eighth day of incubation, the vascular density of the embryos was examined. Following the assessment of vascular development, 4–5 mL of albumin was collected via syringe to measure oxidative stress markers. Each group consisted of 10 embryos, with a total of 40 embryos used in the study. The groups were organized as follows: Control Group (CG), Bevacizumab Group (BC), Trimetazidine 10⁻⁴ Group, and Trimetazidine 10⁻⁵ Group. Results When the total oxidative capacity (TOC) levels were compared among the groups, the bevacizumab group exhibited significantly higher values than the control group (p < 0.05). In oxidative stress index (OSI) measurements, the bevacizumab group also showed significantly higher values compared to the control group (p < 0.05). In contrast, when the total antioxidant capacity (TAC) levels were compared, both the Trimetazidine 10⁻⁴ and Trimetazidine 10⁻⁵ groups demonstrated significantly higher values than the control group (p < 0.05). Regarding angiogenesis scoring, the bevacizumab group exhibited a significant anti-angiogenic effect compared to the control group. However, no statistically significant difference was observed between the Trimetazidine 10⁻⁴ and Trimetazidine 10⁻⁵ groups and the control group (p > 0.05). Conclusion Trimetazidine demonstrated significant antioxidant activity in an in vivo Chorioallantoic Membrane (CAM) model at both 10⁻⁴ M and 10⁻⁵ M concentrations. However, no positive or negative effects on angiogenesis were detected. We believe that the real-time observation of angiogenesis in our study provided significant value to our research.